Struktur Lakon Panji Reni dalam Pagelaran Wayang Topeng Malangan oleh Ki Soleh Adi Pramono - Nasrullah, Ahmad Emir Selby; Susilo, Yohan (Jurnal Online Baradha, 2023)
Abstract Puppet is one of the java being inherited Indonesia culture which must be preserved and be preserved. Puppet show a mask Malangan another type of works of art in which containing a variety of sort of the training and noble values, so that it can be used as conth to live participate in community events. Discussed the theme the research strcture Lakon Panji Reni in show puppet topeng Malangan by Ki Soleh Adi Pramono. Formulation is an issue that is presented (1) how a puppet topeng Malangan the theme Panji Reni the show?, (3) how about characteristic puppet topeng Malangan?, (3) how about structure Lakon Panji Reni?, (4) what are the values containted in the Lakon Panji Reni?. In line with the objectives of the study, this study uses qualitative descriptive. The object of this study is the structure of the Lakon Panji Reni in the puppet show topeng Malangan. Source of research data from (1) data premiere namely youtube channel Arts and culture that covers the performances of the Lakon Panji Reni wayang topeng Malangan, and (2) secondary data sources are Ki Soleh Adi Pramono as puppeteer in wayang topeng Malangan performance, experts/artists, history books, and articles. This study has the purpose of (1) explain the form of puppet mask Malangan in puppet show Mask, (2) explain the characteristics of puppet topeng Malangan, (3) explain the structure of the Lakon Panji Reni, and (4) explain the values contained in the play Panji Reni. The results of this study are the structure of the Lakon Panji Reni, such as plot, theme, characterization, setting, and mandate in the Lakon Panji Reni in wayang topeng Malangan. Keywords : puppet topeng Malangan, Lakon Panji Reni, structure Lakon Panji Reni